Finding a better drug for epilepsy: Antiepileptogenesis targets - Kobow, Katja; Kobow, Katja; Auvin, Stephane; Jensen, Frances; Loescher, Wolfgang; Mody, Istvan; Potschka, Heidrun; Prince, David; Sierra, Alejandra; Simonato, Michele; Pitkaenen, Asla; Nehlig, Astrid; et al. (Epilepsia, 2012)
For several decades, both in vitro and in vivo models of seizures and epilepsy have been employed to unravel the molecular and cellular mechanisms underlying the occurrence of spontaneous recurrent seizures (SRS)the defining hallmark of the epileptic brain. However, despite great advances in our understanding of seizure genesis, investigators have yet to develop reliable biomarkers and surrogate markers of the epileptogenic process. Sadly, the pathogenic mechanisms that produce the epileptic condition, especially after precipitating events such as head trauma, inflammation, or prolonged febrile convulsions, are poorly understood. A major challenge has been the inherent complexity and heterogeneity of known epileptic syndromes and the differential genetic susceptibilities exhibited by patients at risk. Therefore, it is unlikely that there is only one fundamental pathophysiologic mechanism shared by all the epilepsies. Identification of antiepileptogenesis targets has been an overarching goal over the last decade, as current anticonvulsant medications appear to influence only the acute process of ictogenesis. Clearly, there is an urgent need to develop novel therapeutic interventions that are disease modifyingtherapies that either completely or partially prevent the emergence of SRS. An important secondary goal is to develop new treatments that can also lessen the burden of epilepsy comorbidities (e.g., cognitive impairment, mood disorders) by preventing or reducing the deleterious changes during the epileptogenic process. This review summarizes novel antiepileptogenesis targets that were critically discussed at the XIth Workshop on the Neurobiology of Epilepsy (WONOEP XI) meeting in Grottaferrata, Italy. Further, emerging neurometabolic links among several target mechanisms and highlights of the panel discussion are presented.
Keywords: Epileptogenesis; Neuroprotection; Antiepileptic drug; Ion channel; Epigenetics; Neurotrophic factors; Metabolism; Biomarker; Ketogenic diet